Measuring Knowledge Management: A Strategic Approach to Library Information Services - Caldas, Rosangela Formentini [UNESP] (My University, 2012)
In the study of theoretical trends in Administration, the management of information follows the development of theories of Administration; constant-adaptations are suffered. Information Science area understands and concerns itself with the changes wrought in these endeavour of the knowledge society as new forms of communication and integration. The libraries interact in ways that maximize access to information and facilitate the improvement on their structural environment as strategic approach for your services. The research aims at identifying the requirements and specifications of an information system for knowledge management in the public’s library environment and proposes to achieve a pre-defined structure for the implementation of administration management. The research is conducted with public’s library of the metropolitan region of the North’s Portugal. Portugal libraries are institutions that operate in the social process of their communities reflecting the society and its organic sphere of informational performance. These libraries have developed the organizational theories to make a framework easily for effective management practices and have been using their produced knowledge in the optimization of their actions. In the improvement of systems, theoretical administrative trends become management decisions and result in the ultimate success of the organization. In order to achieve its objectives the study verified an economy based on knowledge management, and its production emphasizes the human capital that permeates the condition of the information in support for the development of communities.
Keywords: ciência da informação; cidade inteligente